Serum cytokine profiles in patients with myasthenia gravis - Xuan Wu; Xuan Wu; Huan Huan Song; Guo Rong Xu; Guo Rong Xu; Run Yun Li; Xiao Bin Ye; Xiao Bin Ye (Frontiers in Neurology)
BackgroundCytokines play a crucial role in instigating inflammation and generating pathogenic autoantibodies at the neuromuscular junction in individuals suffering from myasthenia gravis (MG). The objective of this study is to investigate the cytokine profiles among patients grappling with MG.MethodsThis study recruited patients with unstable MG and healthy controls from the First Affiliated Hospital of Fujian Medical University during the period spanning January 2021 to December 2022. We evaluated IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12P70, IL-17, IFN-γ, IFN-α, and TNF-α in the serum using the Flow Cytometric Bead Array (CBA) technique.ResultsA total of 104 patients and 54 healthy controls were included in the study. Notably, serum levels of interleukin (IL)-1β, IL-2, IL-10, and IL-17 exhibited significant elevation in unstable MG patients when compared to the healthy control group. Furthermore, levels of IL-1β and IL-5 were notably higher in unstable MG patients who tested negative for acetylcholine receptor (AChR) antibodies when compared to their AChR-antibody positive counterparts (P < 0.05). In AChR-antibody positive patients, there was a statistically significant decrease in IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL12-P70, IFN-γ, and IFN-α upon improvement. There was no discernible variation in MG patients at an unstable stage regardless of their onset time. Additionally, there was no statistically significant differences between pre- and post-thymectomy in thymoma-associated MG (TAMG).ConclusionIndividuals with unstable MG appear to demonstrate elevated levels of serum IL-1β, IL-2, IL-10, and IL-17 compared to healthy individuals. Furthermore, among MG subgroups, those testing negative for antibodies, tend to display increased levels of IL-1β and IL-5. These serum cytokine profiles may hold promise as potential biomarkers for stratifying MG patients in clinical settings.